Glasgow prognostic score is an independent marker for poor prognosis with all cases of epithelial ovarian cancer. (1st March 2016) - Omichi, Chiaki; Nakamura, Keiichiro; Haraga, Junko; Masuyama, Hisashi; Hiramatsu, Yuji
Abstract: Inflammatory markers are important prognostic factors in various cancers. This study investigated whether inflammatory markers of the Glasgow prognostic score (GPS) predicted progression‐free survival (PFS) and overall survival (OS) for patients with all cases of epithelial ovarian cancer (OC). Pretreatment GPS was examined for the correlations with PFS and OS in 216 patients in all stages of epithelial OC. Statistical analyses were performed using the Mann–Whitney U ‐test. PFS and OS were analyzed using the Kaplan–Meier method. Cox's proportional hazard regression was used for univariate and multivariate analyses. For all patients, the median PFS was 35.1 months, and median OS was 46.7 months; follow‐up range was 1–162 months. Kaplan–Meier analysis revealed that patients with high GPS (GPS 2) at pretreatment had a shorter PFS and OS than did patients with lower GPS (GPS 0 + 1) in for early, advanced, and all‐stages of OC (PFS: P  < 0.001 for early‐, advanced‐ and all‐stages; OS; P  < 0.001 for early‐ and all‐stage, P  = 0.015 for advanced‐stage). GPS (GPS 2) was also found to be an independent predictor of both recurrence ( P  = 0.002) and survival ( P  = 0.001) of all cases of epithelial OC by a multivariate analysis. GPS can serve as an indicator of poor prognosis in patients with all stages of epithelial OC, including early‐stage disease and regardless of histology. Abstract : This study investigated whether inflammatory markers of the Glasgow prognostic score (GPS) predicted progression‐free survival (PFS) and overall survival (OS) for patients with all cases of epithelial ovarian cancer (OC). GPS can serve as an indicator of poor prognosis in patients with all stages of OC cancer, including early‐stage disease and regardless of histology.